Gut opportunistic pathogens contribute to high-altitude pulmonary edema by elevating lysophosphatidylcholines and inducing inflammation - Xianduo Sun; Gaosheng Hu; Yuting Li; Wenjing Li; Yong Wang; Hui Yan; Guoqing Long; Long Zhao; Anhua Wang; Jingming Jia (Microbiology Spectrum)
ABSTRACT Gut microbiota have been found to promote hypoxia-induced intestinal injury. However, the role of gut microbiota in high-altitude pulmonary edema (HAPE), the preventive effect of synbiotic on HAPE, and the mechanisms by which they might work remain unknown. In this study, we aimed to investigate the role of gut microbiota in the pathogenesis of HAPE and to explore the underlying mechanisms involved. We performed a fecal microbiome analysis and found a significant decrease in intestinal Klebsiella and Escherichia-Shigella, along with a notable increase in intestinal Bifidobacterium and Lactobacillus, as volunteers recovered from acute mountain sickness (AMS). Gavage colonization with Klebsiella pneumoniae and Escherichia coli induced plasma inflammation, increased plasma lysophosphatidylcholine (LPC) levels, and contributed to HAPE in rats at a simulated altitude of 6,500 m. Conversely, a synbiotic containing Bifidobacterium, Lactiplantibacillus, fructooligosaccharides, and isomaltose-oligosaccharides significantly reduced the severity of HAPE. Cellular experiments and molecular dynamics simulations revealed that LPCs can cause damage and permeability to human pulmonary microvascular endothelial cell (HPMEC) and human pulmonary alveolar epithelial cell (HPAEpiC) monolayers under hypoxic conditions by disrupting cell membrane integrity. In addition, tail vein injection of LPCs promoted HAPE in mice at a simulated altitude of 6,500 m. In conclusion, this study describes a gut microbiota-LPCs/inflammation-HAPE axis, an important new insight into HAPE that will help open avenues for prevention and treatment approaches.IMPORTANCEThe role of the gut microbiota in high-altitude pulmonary edema (HAPE) is currently unknown. This study found that intestinal Klebsiella pneumoniae and Escherichia coli contribute to HAPE by inducing inflammation and increasing lysophosphatidylcholine (LPC) levels under hypoxic conditions. Conversely, a synbiotic containing Bifidobacterium, Lactiplantibacillus, fructooligosaccharides, and isomaltose-oligosaccharides significantly reduced the severity of HAPE. Further investigation revealed that LPCs can cause damage and permeability to human pulmonary microvascular endothelial cell (HPMEC) and human pulmonary alveolar epithelial cell (HPAEpiC) monolayers under hypoxic conditions by disrupting cell membrane integrity. These findings contribute to the understanding of the pathogenesis of HAPE and will benefit populations living at high altitude or traveling from low to high altitude.